THE DECISION OF PORTUGAL TO LEAVE FROM THE TROIKA’S BAILOUT SCHEMA IN 2014 - Irana Dewi (HI 16 UMY 157, 2016)
*157 Eurozone countries has experienced financial crisis since the 2008, in dealing with the debt crisis / economy in the Eurozone there are three institutions that cooperate institutions, namely Troika there are the International Monetary Fund, European Commission, and European Central Bank. Basically Troika is monitoring countries in severe economic problems that are receiving financial loans provided for by the EU and the IMF. And Portugal is one of the Eurozone country that experience the debt/economic crisis after Greece and Irish, and receive international assistance from Troika (EU-IMF). Portuguese government's decision to ask for help and was negotiations on the bailout program of the troika, Portugal receive financial assistance and must run the schema of the troika, namely the Structural Adjustment Program (SAP) .However for a little over four years of implementation to the SAP program the government decidet to exit from bailout program. The purpose of this research was intended to find out the factors that influence government decisions Portugal To exit the Troika schema. Portugal has been running the bailout program since 2011-2014,on May 17, 2014 Portuguese government declared out of the Troika bailout program and refused further assistance. In this study, using the theory of Two-Level Games where a decisionmaking, the government is faced with international pressure and domestic pressure. International pressure has influence the policy of a country by providing the assistance required by a country to impose terms. and domestic pressures affect policy by pressing the authorities to satisfy their interests. This research method by putting the Portuguese government in the engagement agreement and involves domestic and on international level in making government decisions portugal.